the QUANTITATIVE ANALYSIS OF THE INFLUENCE OF SPIRITUAL ATMOSPHERE AND RITUAL PARTICIPATION ON TOURIST SENSE OF PLACE WITH BAYESIAN ANOVA APPROACH: QUANTITATIVE ANALYSIS OF THE INFLUENCE OF SPIRITUAL ATMOSPHERE AND RITUAL PARTICIPATION ON TOURIST SENSE OF PLACE WITH BAYESIAN ANOVA APPROACH - Dananjaya, Ahmad Ghazy (Ride: Journal of Cultural Tourism and Religious Studies, 2026)
This study aims to empirically examine the influence of spiritual atmosphere and ritual participation on the formation of tourists' sense of place in rural religious tourism destinations in East Nusa Tenggara (NTT). Employing an explanatory quantitative approach, data were collected through a questionnaire survey of 200 respondents selected using purposive sampling technique. Data analysis was performed using SPSS with the Bayesian ANOVA method to measure the strength of evidence for the hypothesis. The results indicate that spiritual atmosphere and ritual participation, both simultaneously and partially, have a significant influence on sense of place. These findings suggest that the stronger the sacred atmosphere and the more active the tourist involvement, the higher their emotional attachment to the destination. This study recommends that destination managers focus on preserving atmospheric authenticity and encouraging active tourist engagement.